Prognostic factors of tumor recurrence in completely resected non-small cell lung cancer - Apichat Tantraworasin (2018)
Background: Patients with completely resected non-small cell lung cancer (NSCLC) have an excellent outcome; however tumor recurs in 30%-77% of patients. This study retrospectively analyzed the clinicopathologic features of patients with any operable stage of NSCLC to identify the prognostic factors that influence tumor recurrence, including intratumoral blood vessel invasion (IVI), tumor size, tumor necrosis, and intratumoral lymphatic invasion. Methods: From January 2002 to December 2011, 227 consecutive patients were enrolled in this study. They were divided into two groups: the "no recurrence" group and the "recurrence" group. Recurrence-free survival was analyzed by multivariable Cox regression analysis, stratified by tumor staging, chemotherapy, and nodal involvement. Results: IVI, tumor necrosis, tumor diameter more than 5 cm, and nodal involvement were identified as independent prognostic factors of tumor recurrence. The hazard ratio (HR) of patients with IVI was 2.1 times higher than that of patients without IVI (95% confident interval [CI]: 1.4-3.2) (P =0.001). The HR of patients with tumor necrosis was 2.1 times higher than that of patients without tumor necrosis (95% CI: 1.3-3.4) (P=Patients who had a maximum tumor diameter greater than 5 cm had significantly higher risk of recurrence than patients who had a maximum tumor diameter of less than 5 cm (HR 1.9, 95% CI: 1.0-3.5) (P = 0.033). Conclusion: IVI, tumor diameter more than 5 cm, and tumor necrosis are prognostic factors of tumor recurrence in completely resected NSCLC. Therefore, NSCLC patients, with or without nodal involvement, who have one or more prognostic factors of tumor recurrence may benefit from adjuvant chemotherapy for prevention of tumor recurrence. © 2013 Tantraworasin et al, publisher and licensee Dove Medical Press Ltd.